Market access, intensification and productivity of Common bean in Ethiopia: a microeconomic analysis - Katungi, E; Horna, D; Gebeyehu, S; Sperling, L. (2011)
This work analyses on-farm adjustments in land allocation and intensification in a commercial crop following the increases in market demand in a developing economy. Drawing from the survey conducted among common bean producers in Ethiopia in 2008, a two stage econometric method was used to investigate the contribution of market access and other micro-level factors in facilitating crop intensification and productivity. Ethiopia is the leading commercial producer and exporter of common bean in Africa but also one of the countries in Africa with high levels of soil nutrient depletion. Understanding factors that influence input use and productivity is critical for food security and agricultural sustainability in the country. Based on farm survey data, it was shown that most farmers had expanded their area under common bean but the use of fertilizer and improved varieties was still low. Increase in the intensity of fertilizer and seed use produces an increase in yield and so is market access. Market access has intensification as well as specialization effects on common bean yield. Access to credit, extension and household wealth are other factors that facilitate common bean intensification while risk increasing factors constrain it.